Wandel von Erwerbsbeteilung westdeutscher Frauen nach der Erstgeburt: ein Vergleich der zwischen 1936 und 1965 geborenen Kohorten - Nadiya Kelle (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
– In the early half of the twentieth century in West Germany the male breadwinner model was dominant with men playing the provider role and women staying at home and taking care of children. The employment of mothers was not a common practice, so that they only worked due to the financial situation of the family or at least justified their labor market activity that way. The present paper deals with the question if and how the employment careers of West German women with at least one child have developed in the process of social change. For this purpose a comparison of three cohorts (1936-45, 1946-55 and 1956-65) is carried out. It is of interest whether and how the employment patterns have changed. Another question is what are the crucial factors affecting the maternal employment and how have they changed with time. The analysis reveals that there are solid employment patterns of mothers, which change across cohorts for instance resulting in more part time employment participation after childbirth. Also the effects of the indicated factors have changed, whereas the marriage as well as the social position have lost their influence on the maternal employment in the process of social change.
Keywords: 330; employment; mothers; childbirth; social change; West Germany; sequence analysis; optimal matching; event history analysis; Weibliche Arbeitskräfte; Erwerbstätigkeit; Mütter; Kinder; Deutschland